Preschool Children in Childcare Settings Do Not Consume a Healthy Diet Despite Menus that Meet Recommended Dietary Standards - Kirk, Stacie M.; Kirk, Erik P. (International Journal of Child Health and Nutrition, 2018)
Purpose/Objective: To compare preschool lunch menus that meet dietary guidelines to what is actually served and consumed. Methods: Fifty-two preschool children (mean±SD, age 3y and 10m ± 8m) from a university early childhood center participated in the 10-week study. Dietary intake was measured by a registered dietitian using direct observation for pre and post meal analysis. Energy and nutrient content was completed using Food Processor Nutrition Analysis by ESHA. Results: There was a significant (p<0.05) difference for total kilocalories (kcals) between what was on the menu (448 ± 130) and to what was served to the children (523 ± 148) compared to what was consumed (361 ± 178) by the children. There was a significant (p<0.05) difference for grams of fat between what food was listed on the menu (16.0 ± 8.7g), the food served to the children (21.2 ± 9.7g), and the food consumed (14.5 ± 10.0g) by the children. There was a significant (p<0.05) difference for grams of carbohydrate between what food was listed on the menu (55.3 ± 18.9g) and the food served to the children (56.5 ± 20.5g) compared to what was consumed (38.5 ± 21.7g) by the children. Children consumed only 46.9% of the vegetables, 88.9% of dairy products, 82.0% of fruits, 81.8% of grains and 72.8% of meats served, and 77.9% of all fats/sweets served to them at lunch. Conclusion: The results indicated that menus that meet recommended dietary standards do not translate into what children are served or consumed, in particular, for vegetables.